Self-accelerating click reaction for preparing cyclic polymers from unconjugated vinyl monomers. (14th February 2018) - Li, Zi; Qu, Lin; Zhu, Wen; Liu, Jian'an; Chen, Ji-Qiang; Sun, Peng; Wu, Ying; Liu, Zhengping; Zhang, Ke
Abstract: An efficient metal-free bimolecular homodifunctional ring-closure method was developed specifically for preparing well-defined cyclic polymers from unconjugated vinyl monomers. In this approach, well-defined homodifunctional linear polymers with azide terminals were prepared by using the reversible addition chain transfer polymerization/macromolecular design by interchange of xanthates (RAFT/MADIX) to polymerize unconjugated vinyl monomers in the presence of a diazide xanthate chain transfer agent. The self-accelerating double strain-promoted azide-alkyne cycloaddition (DSPAAC) reaction was then applied to ring-close the linear polymer precursors with sym -dibenzo-1, 5-cyclooctadiene-3, 7-diyne (DBA) as small linkers, leading to the formation of corresponding cyclic polymers. By virtue of the self-accelerating property of DSPAAC ring-closing reaction, this novel method smartly eliminated the requirement of equimolar amounts of the telechelic polymers and small linkers in the traditional bimolecular ring-closure methods for pure cyclic polymers. More importantly, the usage of excess DBA small linkers could significantly enhance the preparation efficiency of cyclic polymers. Moreover, the cyclic polymers resulted from this novel method could be conveniently cleaved back to linear polymers by a mild aminolysis of the S-C(S) bond within the cyclic polymer backbone. Graphical abstract: Image 1 Highlights: Metal-free homodifunctional bimolecular ring-closure method for cyclic polymers from unconjugated vinyl monomers. Self-accelerating ring-closing reaction requires no stoichiometry between linear polymers and small molecule linkers. Aminolysis can cleave cyclic polymers back to their linear polymer counterparts.